Kombinasi Formulasi Simplisia Serbuk Daun Seroja (Nelumbo nucifera Gaertn.) Dengan Serbuk Rimpang Jahe (Zingiber officinale) Dalam Sediaan Teh Celup Sebagai Minuman Kesehatan - Fitri , Khairani; Khairani , Tetty Noverita; Tarigan , Rida Evalina; Ananda , Sheila Rizka; Arista , Eni (Journal of Pharmaceutical and Sciences, 2025)
Introduction: Indonesia is a tropical country with high humidity that supports the growth of various plants, including medicinal herbs such as lotus leaves and ginger. Objective: This study aims to formulate a combination of powdered lotus leaves (Nelumbo nucifera Gaertn.) and powdered ginger rhizome (Zingiber officinale) into tea bag preparations and to evaluate their quality. Methods: The study employed an experimental method. Testing was conducted based on the Indonesian National Standard (SNI) parameters for tea bags, including organoleptic evaluation, moisture content test, total ash content test, acid-insoluble ash test, water-soluble extractive test, and hedonic test. Results: The concentrations of lotus leaf powder and ginger powder formulated were 100:0 (F0), 90:10 (F1), 80:20 (F2), 70:30 (F3), 60:40 (F4), and 50:50 (F5). The hedonic test results indicated that formula F5 (50:50) was the most preferred by the panelists compared to other formulas, with the highest average score. However, overall, the commercial tea (positive control) still obtained a higher preference score. Conclusion: The combination of lotus leaf powder and ginger rhizome powder was successfully formulated into tea bag preparations. Formula F5 (50:50) was selected as the best among all tested formulations, although its preference level remained lower than that of commercial tea.